Implementation of the Discovery Learning (DL) Model to Enhance the Mathematical Communication Skills - Syadevi, Aulya Revicka Dwi; Heleni, Susda; Siregar, Syarifah Nur (FKIP - Universitas Riau, 2025)
This study aims to improve the quality of the learning process and enhance students’ Mathematical Communication Skills (MCS) through the implementation of the Discovery Learning (DL) model in teaching the Pythagorean Theorem. The participants of this study consisted of 28 eighth-grade students (class VIII_6) from SMPN 3 Tambang. A Classroom Action Research (CAR) design was employed, conducted in two cycles. Each cycle consisted of four phases: planning, implementation, observation, and reflection. The instruments used in this study included the Learning Objectives Flow (LOF), teaching modules, observation sheets, and tests. Data were analyzed using both narrative descriptive analysis and descriptive statistics. The findings indicated that the application of the Discovery Learning model effectively enhanced the quality of the instructional process and significantly improved students’ Mathematical Communication Skills. This was evidenced by an increase in the average MCS score from 72.52 in the first cycle to 87.80 in the second cycle. In conclusion, the Discovery Learning model is proven to be effective in improving students' learning outcomes and developing their Mathematical Communication Skills in class VIII_6 at SMPN 3 Tambang during the first semester of the 2024/2025 academic year on the topic of the Pythagorean Theorem.